Influence of microhabitats on the performance of herbaceous species in areas of mature and secondary forest in the semiarid region of Brazil - Ramos de Andrade, Juliana (2015)
The conditions for plant establishment in mature forest are different from those found in disturbed areas. In dry environments, the herbaceous cover is the most important in the recolonization of deforested areas. It can, therefore, act as an ideal biological group for assessing how changes in habitat heterogeneity affect the resilience of dry forests. The aim of this research was to evaluate whether natural regeneration of the herbaceous stratum differed between areas of mature and secondary forest of Caatinga and to describe this process. The study took place in the Brazilian semiarid region during the rainy season 2011 (January to August), where fifty 1m² plots were set up, 25 allocated to the microhabitat established as “between canopies” and 25 to the microhabitat “under the canopy”. The herbaceous species selected for the study were Delilia biflora (Asteraceae), Gomphrena vaga (Amaranthaceae) and Pseudabutilon spicatum (Malvaceae), abundant species occurring in both areas. All individuals from the selected populations were counted, marked with sequential numbers, and the height of the stem was measured. Differences between areas, and in size and survival between microhabitats, were found only for the first two species. Fruit production was higher in the mature forest for the three species. The study concluded that: 1. The effect of the microhabitats “between canopies” and “under the canopy” in mature and secondary forest areas depends on the species considered; 2. Populations sensitive to light intensity differ in number of individuals, height and fruit production; and 3. The resilience of anthropogenic areas in semiarid environments can be characterized by the presence of spatial heterogeneity with regard to the emergence and survival of herbaceous seedlings, suggesting that the regeneration of disturbed areas may occur in patches.